2021
DOI: 10.1590/1516-3180.2020.0492.r1.0802021
|View full text |Cite
|
Sign up to set email alerts
|

Influence of foot pain on frailty symptoms in an elderly population: a case-control study

Abstract: Aging and chronic illness processes like hyperglycemic disease, musculoskeletal disorders and heart processes can produce frailty syndrome. Consequently, these degenerative processes produce alterations that can affect mental and general health. 1 For example, aging and frailty can affect gait speed and increase the risk of falling due to balance alterations. [2][3][4] Furthermore, the presence of frailty symptoms affects health-related quality of life (HQoL) 5 in this population group.Frailty syndrome can be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
(60 reference statements)
0
3
0
Order By: Relevance
“…The effect of foot care on the population with frailty and foot disorders needs to be explored in greater depth in future studies. Additionally, similar to a previous study that explored the link between frailty syndrome and foot pain (Navarro-Flores et al, 2021), the association between frailty and various foot disorders should be studied in Japan in the future. Further, nail length and skin dryness may improve over a short period; however, toe and arch deformities, and circulation need to be examined over a longer period.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…The effect of foot care on the population with frailty and foot disorders needs to be explored in greater depth in future studies. Additionally, similar to a previous study that explored the link between frailty syndrome and foot pain (Navarro-Flores et al, 2021), the association between frailty and various foot disorders should be studied in Japan in the future. Further, nail length and skin dryness may improve over a short period; however, toe and arch deformities, and circulation need to be examined over a longer period.…”
Section: Discussionmentioning
confidence: 79%
“…Moreover, the foot-care instruments or methods used in previous studies of older people in the community with diabetes were not adequately suited to this population. In future studies, a different study design may be used based on resources presented in previous studies (Navarro-Flores et al, 2018, 2020a, 2020c, 2021Sánchez-Gómez et al, 2020;Simón-Pérez et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found frailty to be associated with various diseases such as cardiovascular disease, diabetes mellitus, COPD, asthma, stroke, foot pain, cognitive impairment, and depression [ 2 , 3 , 4 , 5 ]. These comorbidities are usually found in older people, so frailty status should be evaluated in these patients.…”
Section: Introductionmentioning
confidence: 99%